2023
DOI: 10.1007/s40979-023-00133-4
|View full text |Cite
|
Sign up to set email alerts
|

ENAI Recommendations on the ethical use of Artificial Intelligence in Education

Abstract: Artificial Intelligence (AI) tools are constantly being released into the public domain. As with all new technological innovations, this brings a range of opportunities and challenges for education: primarily for educators and learners. There is an increasing interest in the academic community and beyond to use Artificial Intelligence in Education (AIED) to generate content. This presents opportunities and challenges for academic and research integrity.The European Network for Academic Integrity (ENAI) is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Reviews devoted to AI in education [27][28][29][30][31][32][33][34][35][36][37][38] focus on the evolution, implementation, and improvement of approaches and tools, not on assessing the prospects and challenges that education faces in the era of total artificial "intellectualization" (Figure 2). In late 2022 to early 2023, with the open access to ChatGPT, several discussions about academic integrity when using AI (for example [39,40]) as well as the first recommendations for the education sector [41] appeared.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Reviews devoted to AI in education [27][28][29][30][31][32][33][34][35][36][37][38] focus on the evolution, implementation, and improvement of approaches and tools, not on assessing the prospects and challenges that education faces in the era of total artificial "intellectualization" (Figure 2). In late 2022 to early 2023, with the open access to ChatGPT, several discussions about academic integrity when using AI (for example [39,40]) as well as the first recommendations for the education sector [41] appeared.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…The insistence half a decade after their 2016 publication may seemingly indicate that higher education institutions (HEIs) have been slow off the mark to respond to this issue in an effective way. This ties in with documented concerns to this end on institutional legislative decisionmaking speed in contrast to the fast-paced, evolving GenAI panorama (Foltynek et al, 2023).…”
Section: English Medium Instruction and Academic Dishonestymentioning
confidence: 62%
“…Further research is also needed to understand how scholars currently perceive the role of these tools, and empirical studies conducted so far have shown that opinions vary, ranging from 'changing the role of educators' to 'extending the human brain' (Firat, 2023). Institutions must ensure students grasp the ethical, methodological, and practical implications of GenAI integration into research (Foltynek et al, 2023). Such foundational knowledge will be instrumental as students transition to leadership roles in academic research.…”
Section: Using Foundation Models and Chatgpt For Research Purposesmentioning
confidence: 99%